Tolerancia religiosa romana e intolerancia cristiana en los templos del Alto-Egipto: Raíces y huellas - Aja Sánchez, José Ramón (Gerión. Revista de Historia Antigua, 2008)
The title of this paper condenses one of the characteristics that the late religious fact adopted: as opposed to the tolerance that in general characterized the ancient pagan cults, the Christianity adopted during and after the fourth century the form of an intolerant and intransigent religion. The paper proposes to fix our attention on privileged scenery of observation: Roman and Late Roman Upper Egypt. It is revealing because of the excellent source of information that has survived over there. Because, indeed, it is enough with observing the reliefs that have survived on the facades and walls of the ancient Egyptian temples (Hellenistics and Romans) to see the unequivocal tracks of the fact that we bring up here: the Roman rulers’ absolute assumption of traditional Egyptian religion and the mutilation of Egyptian temples by Christians.